The stranger within / Evelyn Sharminnie S. Vasuthavan - S Vasuthavan, Evelyn Sharminnie (Universiti Teknologi MARA, Kedah, 2023)
Anthology of 203 poems which were contributed by 156 lecturers and academicians from UiTM and other higher learning institutions. This is in fact the largest collection of poems compiled in one anthology.